Baseline Diameter of the Inferior Vena Cava Measured with Sonography in Euvolemic Children and its Relationship to Somatic Variables - Zaoral, Tomas; Kordos, Peter; Nowakova, Marketa; Travnicek, Borek; Zapletalova, Jana; Pavlicek, Jan (Ultraschall in der Medizin (Stuttgart, Germany, 2022)
PURPOSE: To determine normative data for the inferior vena cava (VCI) diameter in euvolemic children and its correlation with different somatic parameters in a pediatric population at one center in Europe. MATERIALS AND METHODS: This prospective observational study enrolled healthy children aged 4 weeks to 18y that visited our outpatient clinic. Weight, height, body surface area, and age were recorded. The children were grouped according to weight, as follows (80 children/group): < 10 kg, 10-19.9 kg, 20-29.9 kg, 30-59.9 kg, and 60-90 kg. Children were placed in a supine position and, during quiet respiration, the maximum and minimum VCI diameters were measured with M-mode ultrasonography. The collapsibility index (CI) was also automatically calculated for each subject: CI = [VCI maximum (expiratory) diameter - VCI minimum (inspiratory) diameter]/VCI maximum (expiratory) diameter. RESULTS: From May 2016 through November 2018 we retrieved data for 415 children that underwent VCI diameter evaluations. 400 children were included (mean age: 7.8y ± 5.8, mean weight: 32 kg ± 24.4, 46 % girls). The VCImax and the VCImin were significantly correlated with age (r = 0.867, p < 0.001, r = 0.797, p < 0.001), height (r = 0.840, p < 0.001, r = 0.772, p < 0.001), weight (r = 0.858, p < 0.001, r = 0.809, p < 0.001), and BSA (r = 0.878, p < 0.001, r = 0.817, p < 0.001). Correlations between the CI and age, weight, height, and BSA were not statistically significant. CONCLUSION: This prospective study provided reference values for sonographic measurements of VCI diameters in euvolemic children and might greatly assist in assessing fluid status in sick children.
Keywords: ultrasonografie; Reference Values; mužské pohlaví; Vena Cava, Inferior; lidé; Child; dítě; Male; vena cava inferior; Europe; Prospective Studies; Ultrasonography; ženské pohlaví; Humans; Evropa; Female; prospektivní studie; referenční hodnoty